2006
DOI: 10.1038/ncpcardio0597
|View full text |Cite
|
Sign up to set email alerts
|

Patent foramen ovale and cerebrovascular diseases

Abstract: Patent foramen ovale (PFO) has been linked to ischemic strokes of undetermined cause (cryptogenic strokes). PFO-a remnant of fetal circulation when the foramen ovale does not seal after birth-can permit microemboli to escape the pulmonary filter into the intracranial circulation, causing stroke. Coexistent atrial septal aneurysm, pelvic deep vein thrombosis and inherited clotting factor deficiencies could potentiate stroke risk in patients with PFO. Transcatheter PFO closure, a minimally invasive procedure, is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 64 publications
0
36
0
1
Order By: Relevance
“…Regular transthoracic echo may fail to identify most cases of PFO, and contrast-enhanced studies, transesophageal echo or transcranial Doppler imaging are more sensitive at detecting the shunt [17]. PFO is associated with interatrial septal aneurysm (IASA) in up to 56% of cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regular transthoracic echo may fail to identify most cases of PFO, and contrast-enhanced studies, transesophageal echo or transcranial Doppler imaging are more sensitive at detecting the shunt [17]. PFO is associated with interatrial septal aneurysm (IASA) in up to 56% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Several retrospective studies found a strong association of PFO and cryptogenic stroke, especially in young patients [18]. Risk factors for stroke in patients with PFO include an increase in PFO diameter, a larger magnitude of right-to-left shunt, and the presence of IASA and deep venous thromboses [17,19]. The mechanisms of stroke may include paradoxical passage of emboli through the shunt, especially after a Valsalva maneuver or in relation to increased pulmonary vascular pressure [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 The transthoracic echocardiogram involves the placement of a transducer on the patient's chest and provides information on how the blood tissue interfaces within the heart and greater vessels. Problems can occur when performing a transthoracic echocardiogram due to adipose tissue, breast tissue, and the client's unwillingness or inability to lie still during the procedure.…”
Section: Diagnosis Of Pfomentioning
confidence: 99%
“…Patent foramen ovale (PFO) is a congenital heart disease characterized by an opening between the right and left atria resulting from incomplete closure of the ostium secundum by the septum secundum 1 . Recent studies have found an increase prevalence of PFO in women with migraine with aura and young adults (less than 55 years old) with so-called "cryptogenic" ischemic stroke [2][3][4][5][6] .…”
mentioning
confidence: 99%